Efficacy of Intense Pulse Light with Triple Combination Cream Versus Triple Combination Cream alone in the Treatment of Melasma - Verma, Anshul; Agrawal, Sudha (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Introduction: Various studies explored the use of intense pulse light (IPL) therapy in treating melasma, but only a few randomized clinical trials have evaluated the combination of triple combination cream (TCC) with IPL so far. Objective: This study compared the efficacy and safety of the combination of IPL and triple combination cream with triple combination cream alone in treating melasma. Material and Methods: Sixty patients with melasma were enrolled in this assessor-blinded, parallel-group randomized controlled study. Thirty patients were treated with IPL (15J/cm2, two sessions at 2-week intervals) and TCC (Hydroquinone 2%, tretinoin 0.025%, fluocinolone acetonide 0.01%) at night and broad-spectrum sunscreen during day time whereas other groups received only TCC and broad-spectrum sunscreen. The median percentage reduction in melasma area and severity index (MASI) and physician’s global assessment scale was assessed at 12-week to determine the efficacy of the treatment. The incidence of adverse effects at each follow-up and relapse at 16-week were also noted during the study period as the secondary outcome measure. Results: The median reduction in MASI achieved at 12 weeks was 48% in the IPL+TCC group and 13.1% in the TCC group from the baseline. The incidence of relapse was seen in 7.14% and 13.04% patients in the IPL+TCC group and TCC alone group respectively at 16 weeks however, this difference was not statistically significant (p<0.05). Conclusion: Our study supports that IPL and TCC are more effective than TCC therapy alone in treating melasma.